Clues from the intestinal mucus proteome of Atlantic salmon to counter inflammation - Kiron, Viswanath; Kathiresan, Purushothaman; Fernandes, Jorge M.O.; Sørensen, Mette; Vasanth, Ghana Kalerammana; Lin, Qingsong; Lin, Qifeng; Lim, Teck Kwang; Dahle, Dalia; Dias, Jorge; Trichet, Viviane Verlhac (Journal of Proteomics, 2022)
publishedVersion